2012
DOI: 10.1136/amiajnl-2011-000705
|View full text |Cite
|
Sign up to set email alerts
|

Standard practices for computerized clinical decision support in community hospitals: a national survey

Abstract: ObjectiveComputerized provider order entry (CPOE) with clinical decision support (CDS) can help hospitals improve care. Little is known about what CDS is presently in use and how it is managed, however, especially in community hospitals. This study sought to address this knowledge gap by identifying standard practices related to CDS in US community hospitals with mature CPOE systems.Materials and MethodsRepresentatives of 34 community hospitals, each of which had over 5 years experience with CPOE, were intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Such efforts, however, require a skilled workforce-a recent survey found that new job roles specific to computerised clinical decision support systems, such as knowledge engineers and analysts, as well as informatics or information services departments and dedicated governance structures, are being created in community hospitals to better customise decision support for the local needs. 41 Clinicians' participation and cooperation with these new processes is valuable in making systems safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Such efforts, however, require a skilled workforce-a recent survey found that new job roles specific to computerised clinical decision support systems, such as knowledge engineers and analysts, as well as informatics or information services departments and dedicated governance structures, are being created in community hospitals to better customise decision support for the local needs. 41 Clinicians' participation and cooperation with these new processes is valuable in making systems safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical decision support systems are designed to improve provider decisions. When well designed and implemented, clinical decision support systems can improve patient safety, clinical workflow, guideline adherence, and quality of care . Evidence suggests that clinical decision support systems may also decrease malpractice events .…”
Section: Methodsmentioning
confidence: 99%
“…Details about the storage and measurements methods were in accordance with the Clinical Practices standards. [22] De nitions…”
Section: Data Collectionmentioning
confidence: 99%